Antibacterial activity of bacteria isolated from earthworm (Pheretima sp.) gut against Salmonella typhi and Staphylococcus aureus: in vitro experiments supported by computational docking - DIRAYAH RAUF HUSAIN; RIUH WARDHANI; ANDI EVI ERVIANI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Husain DR, Wardhani R, Erviani AE. 2022. Antibacterial activity of bacteria isolated from earthworm (Pheretimasp.) gut against Salmonella typhiand Staphylococcus aureus: in vitro experiments supported by computational docking. Biodiversitas 23: 1125-1131. Bacteria have a diverse ecology niche as the effect of a long evolutionary process. They can live along with other organisms as endosymbiont. Research into endosymbiont bacteria began because of their ability to increase host resistance, especially to pathogens. This study aimed to determine the antimicrobial ability of endosymbiont bacterial isolates of earthworms Pheretimasp., Bacillus brevis, and Bacillus choshinensis that inhabit Pheretimasp. were isolated.The isolates were grown on tryptic soy broth media for 24 hours. The isolates were then purified using tryptic soy agar and biochemically tested to ensure both isolates are endosymbiotic bacteria. Antimicrobial activity was tested using agar diffusion methods in pathogenic bacteria, Staphylococcus aureus, and Salmonella typhi. Amoxicillin and chloramphenicol were used as positive controls. The inhibitory test results showed that incubation for 15 days effectively assessed pathogenic bacteria growth inhibition, marked by the largest inhibition zone (21.32 mm for Salmonella typhi and 16.88 mm for Staphylococcus aureus). They were very effective at inhibiting Salmonella typhiand Staphylococcus aureus growths.Endosymbiotic compounds’ had a potential as antimicrobial. The in silico test supports the inhibitory test, which concluded that endosymbiont isolates can be an antimicrobial characterized by low-binding affinity values (-8,6 on tyrocidine) on molecular docking analysis.